Caries experience in university workers: its association with sociodemographic data - Vázquez-Bojórquez, Claudia (2020)
Objective. To evaluate caries experience in university workers and to associate it with sociodemographic data. Methods. It was performed a descriptive cross-sectional, observational and analytic study in university workers from the University of Guadalajara, Mexico. Sociodemographic data was collected through a questionnaire and the DMFT index, through clinical evaluations. Statistical analysis of χ2, T-student, one-way ANOVA and Post-hoc were performed working with CI of 95%. Results. 290 participants agreed to oral examination, the average age of the interviewed workers was 36.2 ± 0.6. Women represented 55.9%. The DMFT of the evaluated sample was 8.3± 5.3. The χ2 analysis of the evaluated age ratio, showed statistical significance (p=0.0001). Similarly, the decay component of the index was increased in the one-way ANOVA test of the male group (p=0,0001) and of those who reside in Tonala (p=0.022). Additionally, an increased number of filled teeth was found in participants with postgraduate education (p=0.001). The smokers group showed statistical significance (p=0.034) in caries index. Conclusions. The broad DMFT index was found at a low level, however, the older age group was significantly different, being at the high level, well above the two younger age groups. The caries component of the DMFT index was significantly lower in the out of the region residents and those who had postgraduate degree (p=0.022 and p=0.02 respectively).